Modify possibilities of the secondary structures prediction method - Špokas, Alvydas; Timinskas, Albertas (Lietuvos matematikos rinkinys, 2003)
It was analyzed dependence of the average accuracy of secondary protein structure prediction on various GOR algorithm modifications. In essence new modification has expanded informational parameter set by taking into account secondary structure of neighboring amino acid. The accuracy of the method with this modification increases almost for 1 percent. This increase in accuracy is quite significant, as the amount of informational parameters increases not much.